American journal of physical anthropology : official publication of the American Association of Physical Anthropologists - American Association of Physical Anthropologists; Stini, William A. (New York : Alan R. Liss, Inc., 1983)
"The American Journal of Physical Anthropology is designed for the prompt publication of original and significant articles on human evolution and variation, including primate morphology, physiology, genetics, adaptation, growth, development, and behavior present and past."
A new dental wear pattern and evidence for high carbohydrate consumption in a Brazilian archaic skeletal population Turner, Christy G., II and Machado, Lilia M. Cheuiche
Includes bibliographical references.
in English
Keywords: Physical anthropology -- Periodicals. Societies. Serials; Antiquities, Prehistoric; Prehistoric peoples